Development of integrated algal ponding systems in the treatment of wine distillery wastewaters - Dekker, Leendert Gideon (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2003)
In South Africa, wastewater disposal in the wine and distilling industry is undergoing a profound transformation as a result of fundamental changes in regulations and license requirements. To deal with this problem conventional Waste Stabilisation Ponding systems have been used by the industry together with irrigation and evaporation disposal practises. Although effective in the evaporation and containment disposal functions, these pond systems are generally not properly designed and/or managed, resulting in overloading and, at times, the generation of seriously offensive odour problems. Preliminary studies on the feasibility of utilising the Advanced Integrated Wastewater Ponding System as a core treatment technology in winery wastewater treatment were conducted. Results indicated that specific problems had to be addressed before successful ponding treatment could be achieved. This research programme undertook an investigation of the performance of a demonstration ponding system treating household sewage, which formed the basis of the research due to limited experience reported on ponds treating wine industry wastewaters. Malfunctions identified were in correlation with the preliminary winery waste ponding survey, which included unstable fermentation pit functions and inadequate nutrient removal. Retrofitting the fermentation pit with a nylon net across the rising water column resulted in improved retention of active anaerobic sludge, especially during periods of system start-up and/or organic overloading. An investigation into nutrient removal utilising algal biomass provided a valuable contribution towards development of an independent nutrient removal system. Harvested algal biomass was passively manipulated to release polysaccharides under anoxic conditions, with subsequent use as a carbon source by denitrifying organisms. Following denitrification, the still viable algal cells were introduced into a High Rate Algal Pond raceway for photosynthetically produced alkalinity. This high pH environment resulted in induced calcium phosphate mineral formation and subsequent precipitation, as well as effective ammonia stripping from the water. Based on the novel positive research outcomes a decision was made to proceed to the construction of a pilot-scale integrated ponding system treating wastewater from a wine lees factory. The system linked the Anaerobic Baffle Reactor, for pre-treatment, with the improved Advanced Integrated Wastewater Ponding System. The potential of this system has shown that a Waste Stabilisation Ponding system can be engineered to treat wine industry wastewaters and thereby effectively reduce the organic and nutrient loads, by using low-cost retrofitted upgrading unit operations. Valuable algal biomass may also be recovered as a by-product of the treatment process.
Keywords: Sewage -- Purification -- Anaerobic treatment; Wine and wine making -- Waste disposal -- South Africa